A methodological concept for phase change material selection based on multi-criteria decision making (MCDM): A case study. (15th December 2018) - Yang, Kun; Zhu, Neng; Chang, Chen; Wang, Daquan; Yang, Shan; Ma, Shengming
Abstract: Phase change material (PCM) have been explored for different applications to increase the energy efficiency and economy. However, the proper PCM selection to meet given requirements generally requires that a compromise is struck between conflicting criteria. This paper attempts to extend multi-criteria decision making (MCDM) method to solve the PCM selection problem. Firstly, the comprehensive appraisal indexes model is established and the subjective and objective weight of the criteria are obtained based on the analytic hierarchy process (AHP) and entropy information method, respectively. Secondly, the optimized combination weight method is adopted to obtain the combination weight. Then, the pre-screened PCMs are ranked using technique for order performance by similarity to an ideal solution (TOPSIS). Finally, the information retrieval is employed to justify the rankings. To demonstrate the applicability of the proposed method, a problem to select the optimal PCM for ground source heat pump (GSHP) integrated with phase change thermal storage (PCTS) system is considered. The result showed that Ba(OH)2 ·8H2 O is the best material for the given case and the GSHP integrated with PCTS system has better economic performance compared to the GSHP system, meanwhile, the proposed method is a simple and practical approach in solving the PCM selection problem. Highlights: Establish the comprehensive appraisal indexes model for PCM selection. Apply the optimized combination weight method to PCM selection. Examine the ranking goal by information retrieval. A case study is provided to show the applicability of the proposed method.